ICT USE AMONG THE STUDENTS OF ENGINEERING COLLEGES IN KERALA (International Journal of Food and Nutritional Sciences, 2022)
The role of Information and Communication Technology (ICT) plays a wider role in teaching-learning activities like, content creation, administrative, formative-summative assessments, student's performance tracking, trainings, knowledge management and knowledge organization. ICT includes a wide variety of technologies, including computers and software learning tools, networking systems and protocols, hand-held digital devices, digital cameras and camcorders, and other technologies, including those not yet developed, for accessing, managing, creating, and communicating information. The focus of this research is to find out the uses of ICT among the students of engineering colleges in Kerala. Both primary and secondary data are extensively used in this study. Then, the primary data was collected through the questionnaire method from the employees. For this study 75 respondents were selected positively. For collecting necessary data, 75 respondents have been collected in Kerala by using convenience sampling method.